Precipitation Method for LTA Zeolite Synthesis and Structural Characterization - Andita, Jessica Shierly; Putri, Amalia Eka; Siswati, Nana Dyah; Suprihatin, Suprihatin; Nurcholis, Fachrul (Politeknik Negeri Malang, 2025)
The demand for large-scale industrial applications of zeolite has driven the development of synthetic zeolite as an alternative to natural zeolite, which is limited by availability and production constraints. This study investigates the synthesis of LTA (Linde Type A) zeolite using a precipitation method, focusing on the effects of stirring time and aging time on zeolite yield and crystallinity. The synthesis process involved preparing sodium aluminate and sodium silicate solutions, followed by controlled crystallization at 80°C for 8h. The resulting zeolite was analyzed using X-Ray Diffraction (XRD) and Scanning Electron Microscopy (SEM) to determine its phase purity, morphology, and Si/Al ratio. The results showed that optimal zeolite yield (24.75%) was obtained with 3h of stirring and 24h of aging. SEM analysis confirmed the cubic morphology characteristic of LTA zeolite, while EDS analysis determined an Si/Al ratio of 1.44, classifying the product as LTA zeolite. These findings highlight the significance of controlled stirring and aging conditions in optimizing zeolite synthesis for industrial applications.